Arabidopsis thaliana SPF1 and SPF2 are nuclear-located ULP2-like SUMO proteases that act downstream of SIZ1 in plant development - Castro, Pedro Humberto (Journal of experimental botany, 2018)
Post-translational modifiers such as the small ubiquitin-like modifier (SUMO) peptide act as fast and reversible protein regulators. Functional characterization of the sumoylation machinery has determined the key regulatory role that SUMO plays in plant development. Unlike components of the SUMO conjugation pathway, SUMO proteases (ULPs) are encoded by a relatively large gene family and are potential sources of specificity within the pathway. This study reports a thorough comparative genomics and phylogenetic characterization of plant ULPs, revealing the presence of one ULP1-like and three ULP2-like SUMO protease subgroups within plant genomes. As representatives of an under-studied subgroup, Arabidopsis SPF1 and SPF2 were subjected to functional characterization. Loss-of-function mutants implicated both proteins with vegetative growth, flowering time, and seed size and yield. Mutants constitutively accumulated SUMO conjugates, and yeast complementation assays associated these proteins with the function of ScUlp2 but not ScUlp1. Fluorescence imaging placed both proteins in the plant cell nucleoplasm. Transcriptomics analysis indicated strong regulatory involvement in secondary metabolism, cell wall remodelling, and nitrate assimilation. Furthermore, developmental defects of the spf1-1 spf2-2 (spf1/2) double-mutant opposed those of the major E3 ligase siz1 mutant and, most significantly, developmental and transcriptomic characterization of the siz1 spf1/2 triple-mutant placed SIZ1 as epistatic to SPF1 and SPF2